(untitled) (Iraqi Journal of Medical Sciences, 2025)
Background: Banknotes are handled by individuals with varying health and hygiene practices and are stored under diverse environmental and personal conditions. Paper currency is widely exchanged for commercial transactions and services, making it a potential vector for the transmission of bacteria. Objective: To evaluate the bacterial contamination of banknotes in circulation in the Al-Anbar Governorate, Iraq. Methods: The study was done between February and April 2023 and analyzed at the Microbiology Laboratories of the College of Medicine, University of Fallujah. A total of 84 samples were collected from seven banknote denominations across four locations. The bacteria were isolated and then identified by VITEK-2 then the antibiotic susceptibility test was done. Results: Among the locations, the butcher shop had the highest number of positive samples 23 (32.1%), followed by the grocery store 21 (29.1%) and Rafidain Bank 18 (25%), while the pharmacy 10 (13.8%) had the fewest. Bacterial identification revealed a predominance of Gram-negative isolates over Gram-positive bacteria. The number of colony-forming units correlated with the locations of positive samples, with the grocery store being the most contaminated. Antibiotic susceptibility testing indicated that while antibiotics such as Imipenem and Ciprofloxacin may remain effective, significant resistance was observed for Ceftriaxone. Conclusion: The study found that currency used in daily life may be a source of bacterial infection. The exchange of banknotes among individuals with different hygiene practices and occupations may facilitate the spread of diseases through contaminated currency. Keywords: Antibiotic resistance, banknotes, currency contamination, disease transmission Citation: Hasan TA. Banknotes as a potential source of transmissible diseases in the Al-Anbar Governorate, Iraq. Iraqi JMS. 2025; 23(1): 32-38. doi: 10.22578/IJMS.23.1.4